The dance : a novel - Walsh, Dan, 1957- (Walsh, Dan, 1957- Restoration series, 2013)
When Marilyn, tired of being the perfect wife, leaves her husband Jim after twenty-seven years of marriage, it will take a devoted transformation to restore their love.